A case report with the peculiar concomitance of 2 different genetic syndromes. Issue 49 (December 2016) - Lerario, Alberto; Colombo, Irene; Milani, Donatella; Peverelli, Lorenzo; Villa, Luisa; Del Bo, Roberto; Sciacco, Monica; Comi, Giacomo Pietro; Esposito, Susanna; Moggio, Maurizio
Abstract: Rationale: Down syndrome (DS) is the most common chromosome disorder in live born infants, affecting several body systems, but usually sparing skeletal muscles. We present the case of a child with coexistence of DS and dystrophinopathy. Only 1 similar case has been reported so far. Patient Concerns: An 8-year-old boy with DS had a history of incidental finding of increased serum creatine kinase levels up to 1775 U/L (normal values 38–174 U/L). He presented no delay in motor development; at the neurological examination, no muscle weakness or fatigability was detected in 2 different evaluations performed over a 6-month period. Diagnoses: Skeletal muscle biopsy revealed marked dystrophic changes with patchy immunostaining for dystrophin. The Duchenne muscular dystrophy gene was screened for deletions by multiplex polymerase chain reaction, but no mutations were found. Sequence analysis of the Duchenne muscular dystrophy gene revealed a splice-site mutation c.1812+1G>A in intron 15 and confirmed a diagnosis of Becker muscular dystrophy. Interventions: The patient has started a specific physiotherapy that avoided any deterioration in motor development and muscular wasting. Outcomes: A multidisciplinary follow-up was initiated. The genetician that followed the patient for DS was supported by the neurologist, the physiotherapist, the pulmonologist, and the cardiologist. Lessons: This peculiar "double trouble" case exemplifies the value of careful clinical evaluation and adequate clinical experience to identify the concomitance of 2 different genetic syndromes in the same patient, and it points out the significance of muscular strength assessment in DS patients to make the most correct prognosis, and, consequently, to organize the best long-term care.